The Silva Mind Control Method - Jose Silva (Pocket Books, 1977)
Based on the 4-day course pioneered by JosÃƒÂ© Silva, this book shows how people have learned to overcome tension, bad habits, emotional insecurity, and even illness with the techniques of Mind Control, and how, with \\\\\\\'creative visualization\\\\\\\', they have mastered the ability to \\\\\\\'see\\\\\\\' what they desire - then make it happen.